The relationship among storytelling, values, and resilience of college students from Eastern and Western cultural backgrounds. Issue 2 (2nd April 2016) - Nguyen, Kate; Stanley, Nile; Rank, Astrid; Stanley, Laurel; Wang, Yonghui
ABSTRACT: Accumulating evidence suggests that storytelling may be related to personal values and provide an important role in promoting resilience. Western (American and German) and Eastern (Chinese and Vietnamese) college students (total n = 845) were asked to respond to survey items on two predictors (storytelling experiences and value preferences) and the outcome resilience. Correlational analysis established significant relationships among storytelling, values, and resilience. The t -test comparisons of Eastern vs. Western mean scores indicated significant cultural differences for storytelling and values, but not resilience. Structural equation modeling found a significant path from storytelling through values to resilience. The final model revealed that college students of Western countries who reported having significant childhood experiences of storytelling preferred openness to change values such as Benevolence, Self-direction, and Stimulation. The results were discussed in terms of the conceptual context.